(untitled) (Medical Forum Monthly, 2020)
Objective: To compare the performance of medical undergraduate students in online and traditional exams and to gauge student satisfaction regarding online exams. Study Design: Cross Sectional study Place and Duration of Study: This study was conducted at the Liaquat National Hospital and Medical College during the period of June-July 2020. Materials and Methods: The target population was second year MBBS students who had given a paper based traditional exam in their first year of medical college and an online exam in second year. Scores of both the exams were compared. Students ‘opinions about the online exam were collected through an online survey. Data was analyzed using SPSS version-17. Results: There were 88 students who had attempted both year 1 and 2 examinations. There were statistically significant differences amongst median scores of both exams [p=0.016]. Out of 78 responses received majority of the students were satisfied with the instructions and felt that the amount of proctoring was sufficient for a fair exam. Students were equally divided in term of technical or connectivity issues and background noise. Regarding the entire online examination most students reported similar concerns i.e. not fully prepared for the exam due to Covid-19 patients at home and lack of resources. As compared to traditional exam students found online exam difficult to attempt due to technical issues such as power outages, internet issues and software glitches. Conclusion: With better performance in an online exam, students still prefer the traditional exam format better than online exams due to several reasons. This highlights the importance of investing in e-learning and e-assessment infrastructure.